2020
DOI: 10.21203/rs.3.rs-40539/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nomogram for Prediction of fatal outcome in Patients with Severe COVID-19: A Multicenter Study

Abstract: Background & Aims: To develop an effective model of predicting fatalOutcome in the severe coronavirus disease 2019 (COVID-19) patients.Methods: Between February 20, 2020 and April 4, 2020, consecutive COVID-19 patients from three designated hospitals were enrolled in this study. Independent high- risk factors associated with death were analyzed using Cox proportional hazard model. A prognostic nomogram was constructed to predict the survival of severe COVID-19 patients.Results: There were 124 severe patien… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…5 Notably, age predicts the conversion rate and mortality of critically ill COVID-19 patients. 6,7 The results also indicated that male patients had longer nucleic acid conversion times. Studies have shown that male COVID-19 patients, especially older male patients, have higher rates of hospitalization, severe illness, and mortality than female patients, suggesting a possible influence of sex hormones on the function of immune cells.…”
mentioning
confidence: 88%
“…5 Notably, age predicts the conversion rate and mortality of critically ill COVID-19 patients. 6,7 The results also indicated that male patients had longer nucleic acid conversion times. Studies have shown that male COVID-19 patients, especially older male patients, have higher rates of hospitalization, severe illness, and mortality than female patients, suggesting a possible influence of sex hormones on the function of immune cells.…”
mentioning
confidence: 88%